Redefinition of Heptapterus (Heptapteridae) and description of Heptapterus carmelitanorum, a new species from the upper Paraná River basin in Brazil - de Carvalho Deprá, Gabriel (2022)
A new diagnosis and a new classification of Heptapterus are provided and a new species, H. carmelitanorum, is described. Heptapterus is diagnosed by the following character combination: adipose fin confluent with the caudal fin; non-bifurcate caudal fin; anal-fin insertion posterior to vertical through adipose-fin insertion; 10–23 anal-fin rays; anal fin not confluent with caudal fin; and extremely elongate body, with a head length of 16.1–24.9%SL. Species included in Heptapterus are H. borodini, H. carmelitanorum, H. carnatus, H. exilis, H. hollandi, H. mandimbusu, H. mbya, H. mustelinus, H. ornaticeps, and H. qenqo. Some of the character states diagnosing H. carmelitanorum among its congeners are the anal-fin insertion less than one eye diameter posterior to a vertical through the adipose-fin insertion (vs. more than one eye diameter in all congeners); the isognathous mouth (vs. slightly to moderately retrognathous, except H. borodini); and the keel formed by ventral procurrent caudal-fin rays shallow, far from reaching anal-fin base (vs. keel formed by ventral procurrent caudal-fin rays deep, continuing almost to the anal-fin base, except in H. borodini and H. hollandi).